Policy or politics: a content analysis of how the network nightly news covered the 2009-2010 health care issue - Winter, LeAnn (Kansas State University, 2011)
Many critics and scholars (e.g. Lippman, 1927, Putnam, 2000, Entman, 1989, McChesney, 2004, Funigiello, 2005), have argued that news media coverage of major political affairs and policy often fails to provided citizens with the information they need to engage in these issues in a thoughtful manner. The style of news utilized by networks as well as choices in framing have been found to have a significant impact on what is covered and how audiences perceive coverage (Bennett, 2005, Patterson, 2000, Prior, 2003, Zaller, 2003, Cappella & Jamieson, 1997, Ibrahim, 2010, ‘T Riet et al., 2009, Bizer & Petty, 2005, Ben-Porath & Shaker, 2010, Domke & Shah, 1995, and Esposito, 1996). According to the PEW Foundation (2010) a large portion of the 2009-2010 healthcare coverage focused on politics and not how the healthcare system functions (policy). This paper explores the coverage of the 2009-2010 heath care issue by the Network Nightly News through the use of a content analysis. For the purpose of this study, the proposed method of Budge et al. (2001) political party platform categories were used to code the content of the broadcast. These 46 codes contained issues that dealt with the policy of health care and the politics surrounding healthcare, as well as positive vs. negative framing. 30 broadcasts were randomly chosen, one day for each month, from the three nightly news networks during the ten months of highest coverage. Each broadcast was divided into “quasi-sentences”, where each sentence was broken down into individual actions. Results illustrate the frequency between policy and political content, and positive and negative content surrounding the 2009-2010 health care issue. KEYWORDS: Framing, Policy, Politics, Health Care Reform, Network Nightly News, Content Analysis, Quasi-Sentence
Keywords: Network Nightly News; Policy; Politics; Healthcare Reform; Framing; Content Analysis; Communication (0459)